Thermoluminescence measurements of eye-lens dose in a multi-centre stereotactic radiosurgery audit. (February 2019) - Alyahyawi, Amjad; Dimitriadis, A.; Jafari, S.M.; Lohstroh, A.; Alanazi, A.; Alsubaie, A.; Clark, C.H.; Nisbet, A.; Bradley, D.A.
Abstract: Stereotactic radiosurgery (SRS), a non-invasive therapeutic technique, seeks delivery of elevated doses of ionizing radiation to precisely defined targets while at the same time preserving surrounding tissue viability. SRS was developed for treatment of various functional abnormalities, extending also to benign and malignant lesions (the latter sometimes referred to as stereotactic body radiation therapy, SBRT). Local tumour control for single and multiple brain metastases at low complication rates is one such outcome. Notable commercial SRS platforms include Gamma Knife and the linac-based systems, Novalis and Cyberknife. Such systems use imaging techniques that include computed tomography (CT) and magnetic resonance imaging (MRI) in localizing SRS targets, down to a small fraction of one mm. With a wide range of platforms for delivery of SRS, greater investigation and standardization is called for. Present work concerns a multi-centre dosimetric audit (20 centres in all), investigating the range of SRS machines and techniques for a single brain metastasis using a series of small dimension detectors (1.55 mm and less) and an anthropomorphic head phantom. With the lens as one of the more radiosensitive tissues, the aim has been to determine the scattered radiation lens dose received during an SRS treatment, as well as the imaging dose received during planning-stage CT-scanning. Custom-designed holders were fabricated to carry three types of thermoluminescence dosimeters: Ge-doped silica fibres, silica glass beads and TLD-100, the latter as a reference dosimeter (being also of larger dimension than the silica-based dosimeters). For reproducible placement of the TLD holders, a bespoke 3D-printed goggle insert was produced for the head phantom. International guidance is to seek reduction in lens dose down to 0.5 Gy. Present results show lens dose values below 0.5 Gy, albeit sometimes to modest degree, there being need to continue to exercise associated due care in SRS planning and delivery. Highlights: Patient eye lens doses evaluated, modeled from stereotactic radiosurgery and CT planning set-ups. Silica-based Ge-doped fibre and glass bead TL dosimeters used to measure doses. Evaluation system used to audit 20 UK hospitals. Doses found to be < 0.5 Gy, below the threshold for deleterious lens effects.